Knowledge exchange in hybrid communities: a social capital-based approach. Evidence from Latvia - Guido Sechi; Jurgis Skilters; Dino Borri; Caterina De Lucia (European Regional Science Association (ERSA), 2012)
The role of ICT accessibility in enhancing regional innovation through knowledge and information exchange is a recently popular and controversial topic in regional science. Opposing views exist, related to the bigger or lesser importance of geographical proximity in knowledge exchange in an age dominated by virtual global channels. Existing studies primarily focus on regions (macro level) as units of analysis, without investigating socio-cognitive dynamics in detail, and rely on doubtful epistemological assumptions (i.e. the equation of information with knowledge). It may be hypothesized that the debate would benefit from: a) analyses focused on the micro (individual) level; b) a more complex formalization of social dynamics, by means of adequate sociological frameworks; and c) a deeper reflection on the nature of cognitive factors at stake. The present paper is aimed at investigating the effectiveness of physical (geographical) and virtual communities on information and knowledge sharing and enrichment in the republic of Latvia. Which kind of links – physical or virtual ones – are more efficient and psychologically real and important is additionally analyzed. The theoretical framework draws on social and cognitive science, combining social capital theory and cognitively oriented semantics. The theoretical model to be tested empirically relies on a complex taxonomy of social capital and a complex epistemology of shareable knowledge. The former takes into account both physical / virtual structural (network) assets and social resources which are embedded in such networks; the latter encompasses relevant dichotomies in applied epistemology history (description / experience; information / belief). Causal links between social capital dimensions (related to physical / virtual channels) and forms of knowledge are hypothesized. The empirical analysis is based on a methodological approach relying on advanced econometrics (structural equation modelling), able to encompass both measurement problems related to the intangible nature of variables under exam, and an assessment of complex cause-effect dynamics. The analysis, which is carried out at the individual level, helps to compare the effect of physical vs virtual networks in enhancing social resources and hence knowledge exchange and enrichment. The obtained results are tested against control variables accounting for social and cultural differences within the national community, in order to verify the sensitivity of results according to intra-society gaps. Such clusters are identified on the basis of considerations related to community and identity views among the citizenship.
Keywords: O3; Z1; C30; 330; social capital; knowledge sharing; communities; structural equation modelling